Prognostic analysis of esophageal cancer patients after neoadjuvant therapy - Dong, Jing; Li, Cheng; Wang, Bingxiang; Li, Yang; Wang, Suzhen; Cui, Hongxia; Gao, Min (Frontiers in Immunology, 2025)
BackgroundNeoadjuvant therapy is widely used for esophageal cancer (EC), but optimal treatment regimens and predictive factors for outcomes remain unclear. This study retrospectively analyzed data from EC patients who underwent neoadjuvant therapy.MethodsThe chi-square test or Fisher’s exact test was utilized to examine differences in general clinicopathological data between treatment benefit groups. Survival analyses were conducted using Kaplan-Meier methods. Cox univariate and multivariate regression analyses were employed to identify independent risk factors affecting overall survival (OS) in EC patients receiving different treatment modalities.ResultsThe study included 175 EC patients who underwent neoadjuvant therapy. Analysis of clinical benefit differences revealed that patients aged < 65 years (P = 0.028) and those with esophageal squamous cell carcinoma (ESCC) (P = 0.027) were more likely to achieve a complete response, while N1 patients more frequently attained an objective response (P < 0.001). OS analysis indicated that patients who did not receive immunotherapy exhibited better survival outcomes compared to those who did (P = 0.002). Patients with pretreatment N3 status demonstrated poorer survival compared to those with N0 (P = 0.004), N1 (P = 0.003), and N2 (P = 0.003) status. Among post-neoadjuvant EC patients who did not receive immunotherapy, those with primary tumors located in the middle esophagus (hazard ratio [HR], 0.181; 95% Confidence interval (CI) = 0.044-0.739; P = 0.017) and lower esophagus (HR, 0.163; 95%CI = 0.032-0.821; P = 0.028) demonstrated a better prognosis compared to patients with tumors in the upper esophagus. Notably, EC patients who did not receive immunotherapy after neoadjuvant therapy and underwent 3-6 cycles of therapy exhibited a poorer prognosis compared to those who received 1-2 cycles (HR, 2.731; 95%CI = 1.187-6.284; P = 0.018).ConclusionsIn conclusion, this study found that immunotherapy did not play a decisive role in neoadjuvant EC therapy. Instead, 1-2 cycles of chemotherapy or chemoradiotherapy were associated with a more favorable prognosis for these patients.